2011
DOI: 10.1074/mcp.m110.006098
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Schistosoma japonicum Schistosomulum Proteins that are Differentially Expressed Among Hosts Differing in Their Susceptibility to the Infection

Abstract: Schistosomiasis is a tropical, parasitic disease affecting humans and several animal species. The aim of this study was to identify proteins involved in the growth and survival of the parasitic forms inside a host. Schistosomula of Schistosoma japonicum were isolated from three different hosts: the susceptible BALB/c mice; the Wistar rats, which have a considerably lower susceptibility; and the resistant reed vole, Microtus fortis. Soluble proteins of the schistosomula collected from the above three hosts 10 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…After several days, the worms migrate to the portal venous system where they pair and mature [25]. During migration, the schistosomula experience a number of morphological changes and physiological adaptations as they develop into mature worms in their definitive hosts [11,25]. They are instantly exposed to and readily targeted by effector elements of the host immune system, and they are known to be the principal target of innate and acquired immunity [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After several days, the worms migrate to the portal venous system where they pair and mature [25]. During migration, the schistosomula experience a number of morphological changes and physiological adaptations as they develop into mature worms in their definitive hosts [11,25]. They are instantly exposed to and readily targeted by effector elements of the host immune system, and they are known to be the principal target of innate and acquired immunity [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The growth and survival of the worms are extremely poor in M. fortis and most of the worms die within 15 days of challenge with cercariae [9]. Different hosts provide a distinct environment for the schistosomes, which affects the survival and development of the parasite [11]. It is possible that M. fortis has a stronger immune response to the schistosomes during the early phases of infection, with more severe pathological lesions.…”
Section: Introductionmentioning
confidence: 99%
“…This requires adaptations for surviving in the different hosts. Comparative proteomic studies in S. japonicum have begun to shed light on some of the adaptations associated with different hosts, by comparing proteomes from the mouse, rat and vole definitive hosts (Hong et al, 2011). These studies have shown different expression patterns of proteins involved in protein, ribonucleic acid and carbohydrate metabolism as well as proteins involved in stress response or cellular movement.…”
Section: Proteomic Insights Into Parasite Biologymentioning
confidence: 99%
“…Gene-specific primers were designed using Primer 5.0 (Table S3). The TPC2L and NADH dehydrogenase genes were used as references for normalization 61,62 . Reaction conditions and cycling protocols were followed as described in the SYBR green tag kit to add the fluorescent tag during every final extension step.…”
Section: Statistical Analyses and Bioinformatic Analysesmentioning
confidence: 99%